Anaplastic pleomorphic xanthoastrocytomas - Review of the literature with reference to malignancy potential - (:unkn) unknown (KARGER, 2004)
Malignancy potential of pleomorphic xanthoastrocytomas (PXAs) has rather been an underestimated reality. We report the case of a 13-year-old boy who presented with signs of increased intracranial pressure. The child had been epileptic since the age of 2. Computed tomography and magnetic resonance scans revealed a huge left frontal mass. At surgery, a subtotal excision was accomplished. Histopathological diagnosis was anaplastic PXA (grade III; WHO, 2000). The tumor showed an increased mitotic index and minimal endothelial proliferation. The patient died 3.5 months later due to a fatal intracranial hemorrhage. A review of the entire PXA literature revealed 15 well-documented cases of PXA with subsequent malignant transformation and 11 cases of primary anaplastic PXA. The prognosis was grim for both subsets of patients. Anaplastic PXAs clearly represent the transition between the original PXA concept and lipidized giant-cell glioblastoma. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: anaplasia; brain neoplasm; MIB-1 protein; pleomorphic xanthoastrocytoma; protein p53; GLIOBLASTOMA-MULTIFORME; FEATURES; GANGLIOGLIOMA; PROGNOSIS